Nitrogen/sulfur dual-doped micro-mesoporous hierarchical porous carbon as host for Li-S batteries - Zhao, Liping; Zhao, Lihe; Zhao, Ye; Liu, Gang (Frontiers in Bioengineering and Biotechnology, 2022)
A simple hydrothermal process employing sucrose and glutathione as the source of carbon and nitrogen-sulfur, respectively, a porous carbon/sulfur composite material doped with nitrogen and sulfur (NSPCS) was synthesized. The detailed structure information of the material was characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and raman spectroscopy. The morphology information was investigated through scanning electron microscopy (SEM) methods. Structure of the pores and pore size distribution were investigated employing N2 adsorption-desorption isotherm. The material was treated thermogravimetrically (TGA) in order to know the weight ratio of sulfur. The synthesized NSPCS composite produced high specific capacity, excellent rate performance and exceptionally good cycle stability when used as the positive electrode in Li-S batteries.